A Comparative Study of Production Performance and Egg Quality Parameters of Naked-Neck and Indigenous Aseel Chicken of Pakistan - Muhammad Usman; A. Basheer; M. Akram; I. Zahoor (Journal of Basic & Applied Sciences, 2014)
The present study was conducted to evaluate production performance and egg quality of four different varieties of native Aseel chicken in comparison with naked neck. A total of 105 adult chickens, 21 birds from each of four varieties of Aseel namely Lakha, Mushki, Peshawari and Mianwali, and 21 birds from naked neck, were maintained separately. The data of daily egg production, daily egg weight and weekly egg quality were calculated for up to ten weeks and analyzed under Completely Randomized Design (CRD) through SAS 9.1 software. Comparison among treatment means were made through Duncan’s Multiple Range (DMR) test. The results showed that egg production of Naked-neck (47.42) was significantly higher (P<0.05) than that of Mushki (34.08), Lakha (31.43), Mianwali (29.59) and Pesahwari (28.7). However,egg weight of Naked-neck (57.52) and Peshwari (55.65) was significantly greater (P<0.05) compared with lakha (54.03), Mushki (53.7) and Mianwali (51.62). Regarding egg quality traits, shell % of Peshawari (13.57) and Nakedneck (13.16) was significantly higher (P<0.05) than that of Lakha (11.89), Mushki (10.19) and Mianwali (9.36). Similarly, Haugh Unit Score of Naked-neck (82.76) and Peshawari (81.95) was significantly greater (P<0.05) than other varieties of Aseel. Albumen % was significantly higher in Mushki (61.83) variety (P<0.05) while yolk % was significantly higher in Mianwali (59.36) variety of Aseel (P<0.05) whereas yolk index showed non-significant (P>0.05) difference in Naked-neck and all varieties of Aseel.